From morphology to phylogeny (on the example of study of the fish leeches of Palearctic) - Епштейн, В. М. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
The article considers the methodology of cognition of the fauna of the fish leeches (Hirudinea, Piscicolidae) of Palearctic – from description of their appearance to description of the structure of the major organs systems, and more – to construction of a classification of the family at the levels of subfamilies and tribes, to understanding their zoogeography and to working out phylogenetic hypotheses.